Kipczacki materiał leksykalny w słowniku Petera Simona Pallasa (1787-1789) - Kozera-Sławomirska, Izabela (2022)
KIPCHAK LEXICAL MATERIAL IN THE DICTIONARY BY PETER SIMON PALLAS (1787–1789)The dissertation focuses on Peter Simon Pallas’s dictionary Linguarum totius orbis vocabularia comparativa; augustissimae cura collecta (1787–1789) (Sravnitelʹnye slovari vsekh iazykov i narechii). Pallas, an outstanding natural scientist, was the creator of the first comparative dictionary, which is a valuable source on the naming and distribution of Turkic languages and dialects spoken in the territory of the Russian Empire in the 18th century. A semantic and grammatical analysis is undertaken of the Kipchak lexical material recorded by Pallas, which is the most abundant among the Turkic vocabularies contained in his dictionary. The lexis of nine Kipchak languages includes a total of 285 dictionary entries and 3,287 lexical units. The detailed study of selected semantic fields and grammatical classes has identified semantic changes and phonetic features typical of Kipchak languages. The comprehensive approach to the topic adopted in the dissertation opens further research avenues, especially as regards languages which do not have a rich lexicographical tradition.